Cassava - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1989)
Work with cassava in CIAT`s Biotechnology Research Unit covered 2 major areas: in vitro culture techniques and techniques for the analysis of genetic variability. Work was carried out on virus elimination, micropropagation, and germplasm exchange and conservation as well as on the development of plant regeneration techniques from somatic and gametic tissues. Isozyme electrophoretic techniques were developed to assess the genetic variability of germplasm accessions and monitor the stability of clones maintained in vitro. Personnel from national institutions in Latin America and Asia was also trained, in collaboration with scientists from CIAT`s Cassava Program and from research institutions in developed and developing countries. In 1988, a joint exercise was also conducted with the Cassava Program to identify priority cassava research constraints which may be amenable to advanced research and biotechnological solution. An advanced cassava research network was established as an effective means for advancing basic research and developing biotechnology applications to cassava. (CIAT)